Advances in Waveguide Bragg Grating Structures, Platforms, and Applications: An Up-to-Date Appraisal - Muhammad A. Butt; Nikolay L. Kazanskiy; Svetlana N. Khonina (Biosensors, 2022)
A Bragg grating (BG) is a one-dimensional optical device that may reflect a specific wavelength of light while transmitting all others. It is created by the periodic fluctuation of the refractive index in the waveguide (WG). The reflectivity of a BG is specified by the index modulation profile. A Bragg grating is a flexible optical filter that has found broad use in several scientific and industrial domains due to its straightforward construction and distinctive filtering capacity. WG BGs are also widely utilized in sensing applications due to their easy integration and high sensitivity. Sensors that utilize optical signals for sensing have several benefits over conventional sensors that use electric signals to achieve detection, including being lighter, having a strong ability to resist electromagnetic interference, consuming less power, operating over a wider frequency range, performing consistently, operating at a high speed, and experiencing less loss and crosstalk. WG BGs are simple to include in chips and are compatible with complementary metal-oxide-semiconductor (CMOS) manufacturing processes. In this review, WG BG structures based on three major optical platforms including semiconductors, polymers, and plasmonics are discussed for filtering and sensing applications. Based on the desired application and available fabrication facilities, the optical platform is selected, which mainly regulates the device performance and footprint.